Coupling of dietary phosphorus and growth across diverse fish taxa: a meta‐analysis of experimental aquaculture studies. Issue 10 (1st October 2014) - Benstead, Jonathan P.; Hood, James M.; Whelan, Nathan V.; Kendrick, Michael R.; Nelson, Daniel; Hanninen, Amanda F.; Demi, Lee M.
Abstract : Imbalances in phosphorus (P) intake relative to demand negatively affect animal growth, but their consequences are less understood for vertebrates, in which bone represents a significant and potentially flexible pool of P. Flexibility in body‐P content could buffer vertebrates from the effects of imbalances between P intake and demand, reducing the likelihood of a sharp stoichiometric "knife‐edge" in the relationship between growth rate and diet‐P level. We conducted a meta‐analysis of published aquaculture experiments that tested effects of diet %P on fish growth rate (49 studies, 28 species) and body‐P content (27 of the studies in the main data set, 20 species). Our meta‐analysis revealed significant P limitation of growth, as well as significant negative effects of excess P on growth rate. Diet‐P thresholds for these effects occurred at ecologically relevant levels (optimal diet‐P of 1.2% ± 0.45%, mean ± SD, under experimental conditions of high ration). Finally, the analysis also suggested a pattern of relatively shallow relationships between growth rate and diet‐P level, coupled with surprisingly flexible body‐P content in fishes. This result is consistent with fish using flexible body‐P content (presumably mediated through bone P) to buffer imbalances between P intake and demand. Together, our results provide evidence for a relatively "dull" stoichiometric "knife‐edge" in fishes, driven in part by flexible body‐P content.